DEAD TO THE WORLD: EMBODIED GENDER TRANSGRESSION AND THE LOSS OF HUMANITY - Lowrey, Kestryl (eTopia, 2008)
The accepted scope of humanity, though broad on first glance, actually represents a narrow, shallow stream. Within Western culture, the expectations, proscriptions and limitations tied to one’s own “human” status remain largely unidentified until they are transgressed. The human body (lynchpin of humanity) is considered something not to be tampered with, at risk of the loss of one’s human status. While some forms of modification, such as plastic surgery, tattooing, and piercing have become more broadly accepted, more extreme modifications of the body, intentional or otherwise, can render the subject as a freak—an implicit social death. Here emerges a curious overlap between the freak and the spectre, both inhabiting a liminal space between inhuman and exhuman, hypervisible in their distance from humanity. Broadly conceived of as mutilated or desecrated, transgender bodies are alternately read as cultural freaks and social specters, demonstrating the loss of humanity that occurs when transgression is physically written onto the body.